Heritability and path coefficient analysis for quantitative traits of rapeseed advanced lines (Journal of Oilseed Brassica, 2026)
This study was undertaken to examine phenotypic, and genetic variability, broad-sense heritability, genetic gain under selection, and interrelationships of some agronomic traits of rapeseed genotypes. Genotypes showed significant variation for all studied characters. High heritability, and genetic advance estimates were recorded for days to flowering, and seeds per pod indicating the existence of additive gene action for the expression of these traits. High value of heritability, and moderate value of genetic advance were observed for days to end of flowering, and days to maturity suggesting the involvement of non-additive(dominance or epistatic) gene effect for these traits. For all traits, genetic variances were lower as compared to phenotypic ones, demonstrating the environmental influence in their expression. The direct effect of days to flowering (0.35*), pods on main raceme (0.36*), pods per plant (0.56**), and seed yield were positive, and significant, therefore these traits can be used as indirect selection criteria for improving seed yield. The positive association between oil content, and seed yield per plant indicate the possibility of improving these most important traits in rapeseed simultaneously. Among the genotypes, G6, G7, G5, G14, G19, and G21 with seed yield of 3053, 3070, 3094, 3113, 3338, and 3415 kg ha-1, respectively were higher yielding than other genotypes.